Effect of dripper discharge rates and irrigation schedules on yield of cabbage (Brassica oleracea L var capitata) - Pragna G; Manoj Kumar G; Shiva Shankar M (International Journal of Life Sciences, 2017)
The field experiment was conducted during rabi season, 2015-16 in split plot design with three replications. Two irrigation levels namely 0.6 ETc (I1)and 0.8 ETc (I2) as Main plot treatments and four discharge rates 1.6 lph (D1), 2.2 lph (D2), 3.0 lph (D3) and 4.0 lph (D4) were planned as Sub treatments with a total of 24 plots. The cabbage yield (t/ha) was maximum when the crop was irrigated with the drip at 0.8 ETc (29.85 t/ha) which was significantly superior over the crop irrigated with drip at 0.6 ETc (28.35 t/ha). The crop which was irrigated at 1.6 lph (Lowest discharge rate) has recorded significantly highest yield (32.43 t/ha) followed by 2.2 lph (30.08 t/ha), 3.0 lph (28.12 t/ha) and the lowest yield was recorded at the discharge rate of 4 lph (25.75 t/ha). Among two irrigation levels (0.8 ETc and 0.6 ETc), crop irrigated at 0.8 ETc gave higher yield but water use efficiency was higher for crop irrigated at 0.6 ETc. Hence irrigation water could be saved by irrigating the cabbage crop at 0.6 ETc without compromising for the yield.